2002
DOI: 10.1034/j.1600-0412.2002.810804.x
|View full text |Cite
|
Sign up to set email alerts
|

New rapid bed‐side test to predict preterm delivery: phosphorylated insulin‐like growth factor binding protein‐1 in cervical secretions

Abstract: The presence of cervical phIGFBP-1 is predictive of preterm delivery < 37 weeks of gestation. Our study shows that cervical detection of phIGFBP-1 by immunochromotography is a rapid and easily applicable test that highly anticipates preterm delivery in patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 15 publications
2
48
1
2
Order By: Relevance
“…A total of 43 studies, including 10,203 women, met the inclusion criteria, of which nine provided data on asymptomatic women (n=6131), 36-44 28 on symptomatic women (n=3212), 18,45-71 and six on both asymptomatic (n=452) and symptomatic (n=408) women. 17,72-76 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 43 studies, including 10,203 women, met the inclusion criteria, of which nine provided data on asymptomatic women (n=6131), 36-44 28 on symptomatic women (n=3212), 18,45-71 and six on both asymptomatic (n=452) and symptomatic (n=408) women. 17,72-76 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies (47%) were performed in European countries, 16 (37%) in Asia, three (7%) in South America, and four (9%) in Canada. The sample size ranged from 18 72 to 4984 40 (median, 88) in asymptomatic women and from 30 57 to 350 69 (median, 70) in symptomatic women. Among the 34 studies performed in symptomatic women, only seven (21%) defined preterm labor as the presence of uterine contractions with evidence of cervical changes.…”
Section: Resultsmentioning
confidence: 99%
“…It leaks into cervical secretions when fetal membranes detach from decidua. Studies have shown that a bedside rapid strip test (Actim Partus Test) for detection of IGFBP-1 in cervical secretions provides an additional diagnostic tool for the assessment of patients presenting with preterm labour [26, 27]. In another study in which cervicovaginal sample was collected at 22-23 weeks, IGFBP-1 > 6.4  µ g/L had a likelihood ratio of +1.8 (95% CI 0.7–2.9) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to predict preterm delivery have classically been based on history and examination findings only. But these risk assessment scores have poor predictive values [2, 3]. Some studies have found cervical length as measured by transvaginal ultrasound and cervicovaginal IGFBP-1 as most strongly and consistently associated with subsequent spontaneous preterm birth [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, measurement of phIGFBP-1 from cervical secretions can also be used to estimate the ripeness of the cervix [138]. Lembet et al [139] show that for women between 20 and 36 weeks gestation, that phIGFBP-1 has a PPV of 83.3% and a NPV of 94.1% for predicting delivery within 7 days and thus is a useful test for the assessment of the likelihood of preterm delivery.…”
Section: Insulin-like Growth Factor Binding Proteins (Igfbp)mentioning
confidence: 97%